Pengembangan Self Esteem Melalui Pembelajaran Kooperatif - Robingatin, Robingatin (IAIN Samarinda, 2012)
Children with high self esteem are characterized by positive views towards themselves in some dimensions such as physical, academic, and social competence as the basis of their confidence, to make children appreciate themselves, bring sense of secure, and accepted by their friends or others. Children with high self esteem will judge their friends or others same as they are. Self esteem development by a teacher is done to serve children with respect, to help them success in school, to serve children without discrimination, threat, humiliation, and discouragement. Children self esteem development can be done through cooperative learning that teach cooperative principles and skills, establish community in the class, develop positive relationship among friends, tolerance towards the differences which simultaneously develop academic competence.